In vivo evaluation of the subject-specific finite element model for knee joint cartilage contact area - Kang, Kyoung-Tak; Kim, Sung-Hwan; Son, Juhyun; Lee, Young Han; Chun, Heoung-Jae (International journal of precision engineering and manufacturing, 2015)
In this paper, we present a new validation method for subject-specific finite element (FE) modeling of the knee joint based on in vivo computed tomography (CT) and magnetic resonance imaging (MRI) data. Previously, several FE models have been developed for estimating the mechanical response of joint structures, where direct or indirect in vivo measurement is difficult or impossible. More recently, studies using MRI have provided clear visualization of the motion and deformation of the articular cartilage within the tibiofemoral (TF) joint space. Two methods have been introduced to validate in vivo subject-specific models: alignment of supine MRI with X-ray images and weight-bearing MRI. The size of the contact area between the femur and tibia was determined by computing the area of femoral cartilage that intersected the tibial cartilage. The result showed good agreement between non-weight bearing image aligned with X-ray and weight-bearing MRI images. This study may help to better define the relative importance of modeling validations for the development of subject-specific models.